Plasmablastic Lymphoma, a Rare Entity in Bone Marrow with Unusual Immunophenotype and Challenging Differential Diagnosis. (2nd September 2019) - Al Shaarani, Majd; Shackelford, Rodney E.; Master, Samip R.; Mills, Glenn M.; AlZubaidi, Yasir; Mamilly, Ahmed; Wei, Eric X.
Abstract : Plasmablastic lymphoma (PBL) is an aggressive malignancy that usually occurs in the setting of immunosuppression. The immunohistochemical profile of PBL is that of terminally differentiated B lymphocytes. CD138, CD38, and MUM1 are usually immunopositive. However, pan B-cell markers such as CD20 and PAX-5 are usually negative. MYC rearrangement is the most commonly encountered genetic alteration, with immunoglobulin ( IG ), especially immunoglobulin heavy ( IGH ) chain, being the most frequent partner. We report a case of PBL in a 48-year-old human immunodeficiency virus- (HIV-) positive male who was admitted to the hospital with signs and symptoms suspicious for tumor lysis syndrome. Bone marrow examination revealed hypercellular marrow with trilineage hypoplasia and sheets of intermediate to large neoplastic cells with basophilic vacuolated cytoplasm comprising the majority of cellular elements of the bone marrow. The neoplastic cells were negative for conventional B-cell, T-cell, plasma cell, and myeloid markers, while flow cytometric analysis revealed an abnormal CD45-dim population that was partially weakly positive for CD71 and CD79b. The diagnosis was initially thought to be a high-grade primitive hematopoietic neoplasm, possibly an acute undifferentiated leukemia. BOB-1, however, was immunopositive in the neoplastic cells, confirming its B-cell origin. MYC was positive by immunohistochemistry and break-apart FISH, as were CD45, MUM-1, and EMA immunostains. There was immunoglobulin kappa ( IGK ) light chain gene rearrangement by polymerase chain reaction (PCR). Additionally, Epstein–Barr virus- (EBV–) encoded small RNAs (EBER) were positive by in situ hybridization (ISH). The tumor proliferation index by Ki-67 immunostaining approached 95%. Although the tumor cells were negative for CD38 and CD138, the diagnosis of PBL was still rendered. We recommend using a broad spectrum of B-cell markers, including BOB-1 and OCT-2, in such challenging cases of B-cell lymphomas with no expression of conventional B-cell markers. We also emphasize that the negative CD38 and CD138 should not exclude PBL from the differential diagnosis.